Efficacy of Bovine Colostrum in The Treatment of Acute Diarrhea in Infants and Children - Hameed, Hira; Rafique, Aummara; Nadia Tariq; Zulfiqar, Rubina; Aslam, Sohail; Zholdabeskova , Ainur (Journal of Rawalpindi Medical College, 2025)
Objective: The objective of this study was to determine the efficacy of bovine colostrum for the treatment of acute diarrhoea among infants and children admitted to a tertiary care hospital in Islamabad, Pakistan. Methods: This interventional study was conducted at a tertiary care hospital, Islamabad. Infants and children admitted to the hospital with acute diarrhoea were selected through consecutive sampling. Group A received bovine colostrum along with the standard treatment, whereas group B received standard treatment alone. Number of days to achieve defecation frequency of <3 Times per day, normal stool consistency, and duration of hospital stay were the main outcomes of interest. SPSS version 21 was used for statistical analysis. Result: Mean recovery time in Group A was 1.4865+ 0.506 days and in Group B was 1.2174 + days. The mean number of days remaining for patients admitted in Group A was 3.8919 + 1.629 days, while in Group B it was 3.8261+ 1.64 days. The efficacy was 33.59 in group A, while 25.52 in group B. This difference was not statistically significant (p=0.738). Conclusion: There was no difference between the group taking standard treatment and the one taking standard treatment plus bovine colostrum in terms of recovery time and efficacy but the difference was significant in terms of the number of days patients remained admitted where bovine colostrum group had increased no of days of admission so conclusion is there is not much role of bovine colostrum in treatment of acute diarrhea when combined with standard care.